Isotopic analysis to quantify the role of the Indian monsoon on water resources of selected river basins in the Himalayas. Issue 11 (9th November 2021) - Jeelani, Ghulam; Shah, Rouf Ahmad; Deshpande, Rajendrakumar D.; Dimri, Ashok P.; Mal, Suraj; Sharma, Anupam
Abstract: Western disturbances (WDs) and Indian summer monsoon (ISM) led precipitation play a central role in the Himalayan water budget. Estimating their contributions to water resource is although a challenging but essential for hydrologic understanding and effective water resource management. In this study, we used stable water isotope data of precipitation and surface waters to estimate the contribution of ISM and WDs to the water resources in three mountainous river basins ‐ Indus, Bhagirathi and Teesta river basins of western, central and Eastern Himalayas. The study reveals distinct seasonality in isotope characteristics of precipitation and surface waters in each river basin is due to changes in moisture source, hydrometeorology and relief. Despite steady spatial variance in the slope and intercept of regression lines from the Teesta to Indus and the Bhagirathi river basins, the slope and intercept are close to the global meteoric water line and reported local meteoric water line of other regions in the Himalayas and the Tibetan Plateau. The two‐component end‐member mixing method using d‐excess as tracer were used to estimate the contribution from ISM and WD led precipitation to surface water in aforementioned river basins. The results suggest that the influence of the ISM on the water resources is high (>72% to annual river flow) in Teesta river basin (eastern Himalayas), while as the WDs led precipitation is dominantly contributing (>70% average annual river flow) to the surface waters in the Indus river basin (western Himalayas). The contribution of ISM and WD led precipitation in Bhagirathi river basin is 60% and 40%, respectively. The findings demonstrate that the unusual changes in the ISM and WD moisture dynamics have the potential to affect the economy and food security of the region, which is dependent on the availability of water resources. The obtained results are of assistance to policy makers/mangers to make use of the information for better understanding hydrologic response amid unusual behaviour of the dual monsoon system over the region. Abstract : Distribution of stable water isotopes of natural waters in Indus, Bhagirathi and Teesta basins of the Himalay.